ANALISIS PELUANG BANK PERKREDITAN RAKYAT DI JEMBER MENGALAMI KESULITAN LIKUIDITAS - Asih, Dessy Novitasari Laras (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract : Status can bank said liquidity problems at the time of NPL greater than 5%. NPL shows that the ability of bank management to manage problem loans granted by banks.Liquidity problems are very likely to occur in the BPR. Prior to the bankruptcy, it needs to be known in advance about the financial state of the banking system. This study aims to assess the financial ratios in CAMEL can be used to analyze the probability of BPR in Jember experiencing liquidity problems or not. This research is explanatory research with census approach, which is to examine opportunities liquidity difficulties at BPR in Jember based on information published financial statements BPR. From the results of the study showed that the financial ratios that can analyzed probability BPR in Jember likely experiencing liquidity problems that APYDTAP, ROA and LDR the first quarter before. BPR in Jember can be detected experiencing liquidity difficulties during the first quarter before.Keywords: liquidity problems, CAMEL, BPR